2016
DOI: 10.1016/j.dadm.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive variability—A marker for incident MCI and AD: An analysis for the Alzheimer's Disease Neuroimaging Initiative

Abstract: IntroductionThe potential of intra-individual cognitive variability (IICV) to predict incident mild cognitive impairment (MCI) or Alzheimer's disease (AD) was examined and compared to well-established neuroimaging and genetic predictors.MethodsIICV was estimated using four neuropsychological measures for n = 1324 Alzheimer's Disease Neuroimaging Initiative (ADNI) participants who were cognitively healthy or diagnosed with MCI at baseline. IICV was used to predict time to incident MCI or AD, and compared to hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 40 publications
5
45
0
Order By: Relevance
“…In contrast, predicted IICV increased with age at higher literacy levels (and for both sexes), suggesting probable worsening in memory and/or executive function relative to premorbid verbal abilities. This pattern corresponds to other studies that have shown that higher IICV (calculated using variables similar to those we used) predicts MCI, AD or AD pathology ((E. D. Anderson et al, 2016; Gleason, Norton, Anderson, Wahoske, Washington, Umucu, Koscik, Dowling, Johnson, Carlsson, et al., 2017; Holtzer et al, 2008; Koscik et al, 2016)). The former pattern suggests that future studies could examine whether the risk-indicating value of IICV varies across underlying characteristics such as sex and literacy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, predicted IICV increased with age at higher literacy levels (and for both sexes), suggesting probable worsening in memory and/or executive function relative to premorbid verbal abilities. This pattern corresponds to other studies that have shown that higher IICV (calculated using variables similar to those we used) predicts MCI, AD or AD pathology ((E. D. Anderson et al, 2016; Gleason, Norton, Anderson, Wahoske, Washington, Umucu, Koscik, Dowling, Johnson, Carlsson, et al., 2017; Holtzer et al, 2008; Koscik et al, 2016)). The former pattern suggests that future studies could examine whether the risk-indicating value of IICV varies across underlying characteristics such as sex and literacy.…”
Section: Discussionsupporting
confidence: 91%
“…Given recent results in WRAP and other studies suggesting that higher intraindividual cognitive variability (IICV) across tests at a given visit predicts increased risk of subsequent decline or AD pathology (Anderson et al, 2016; Gleason, Norton, Anderson, Wahoske, Washington, Umucu, Koscik, Dowling, Johnson, & Carlsson, 2017; Holtzer, Verghese, Wang, Hall, & Lipton, 2008; Koscik et al, 2016), we also characterized how IICV varied by sex, literacy, APOE, and age in our sample. Specifically, we calculated “4-Test IICV” as the standard deviation of z-scores of AVLT Total and Delay, Trails B, and the Wide Range Achievement Test (3 rd ed., “WRAT”) reading recognition subtest standard score (Wilkinson, 1993); AVLT Delay, Trails B, and WRAT were Box-Cox transformed prior to z-scoring (AVLT Delay had a constant of 1 added to all scores before transformation) The WRAT Reading score when used in middle-aged and older adults is accepted as a stable proxy for premorbid verbal abilities and quality of education (Ashendorf, Jefferson, Green, & Stern, 2009; Manly et al, 2003; Olsen, Fellows, Rivera-Mindt, Morgello, & Byrd, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Multiple potential biomarkers have been identified to aid in the prediction of conversion of MCI to AD. For example, cognitive and behavioral biomarkers have been proposed to identify individuals at high-risk for conversion [11-13]. In addition, biomarkers based on brain imaging or measurements in bodily fluids have been identified (for recent reviews see [14, 15]).…”
Section: Introductionmentioning
confidence: 99%
“…In our data, lower literacy was associated with steady age-related decline in 4-Test IICV with higher IICV consistently observed among women; at higher literacy levels, IICV was generally higher among men and increased with age for both sexes. Our 4-Test IICV is the same as used in previous WRAP analysis and similar to what has been used in other analyses (Holtzer et al, 2008;Anderson et al, 2016, Gleason et al, 2017 which indicate higher IICV predicts MCI and AD. As IICV is developed further as a potential cognitive marker for risk of later decline in the AD continuum, future studies should examine whether riskindicating value is constant across underlying demographics such as age, sex, and literacy.…”
Section: Discussionmentioning
confidence: 80%
“…Given recent results in WRAP and other studies suggesting that higher intraindividual cognitive variability (IICV) at a given visit predicts increased risk of subsequent decline (E. D. Anderson et al, 2016;Gleason et al, 2017;Holtzer, Verghese, Wang, Hall, & Lipton, 2008;Koscik et al, 2016), we also characterized how IICV varied by sex, literacy, APOE, and age in our sample. We calculated two versions of IICV.…”
Section: Study Protocol and Outcomesmentioning
confidence: 93%